Case reportSuspicion of pulmonary embolism during treatment of pemphigoid gestationis - Podolec-Rubiś, Magdalena; Wołek, Marta; Brzewski, Paweł; Wojas-Pelc, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Pemphigoid gestationis (PG), first described in 1872 by Laws Milton, is a rare autoimmune bullous disease of pregnancy and puerperium. Pemphigoid gestationis has been estimated to occur in 1 : 50 000 pregnancies and usually presents in the second or third trimester with exacerbation after partum. This disease is caused by circulating IgG1 immunoglobulin against hemidesmosomal protein bullous pemphigoid BP180 (BPAG2) type XVII collagen and less frequently BP230. We present a case of pemphigoid gestationis in primigravida with complications during treatment due to the suspicion of pulmonary embolism.